University Social Responsibility in the Organizational Happiness Management - CHUMACEIRO HERNÁNDEZ, ANA CECILIA; HERNÁNDEZ GARCÍA DE VELAZCO, JUDITH JOSEFINA; RAVINA RIPOLL, RAFAEL; REYES HERNÁNDEZ, IVANA V. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Social responsibility today has acquired a significant place before society; this does not escape organizations, whatever their nature. The university, as a social organization, must seek a very stable position in this area since the ultimate goal of responsibility is the common good. In this tonic, this article intends to identify theoretically how from the university organizations, and the social responsibility that derives from them, management of organizational happiness can be done. The systematic review of documents and hermeneutical analysis constituted the method, which allowed us to reflect on everyday university practice. For being consistent with the context, an ontological and axiological commitment must be developed from the university towards the social demands that surround it. Resulting in high levels of motivation. Which benefit from day-to-day activities, as well as more productive individual and group work dynamics.